Structure-conduct-performance of the Malaysian poultry industry - Muazu, Abdulrazak Umar; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir; Abd. Latif, Ismail (American-Eurasian Network for Scientific Information, 2013)
This study considers the structure conduct performance (SCP) model to assess degree of competition in the supply chain of the Malaysian poultry market. Malaysian Poultry industry Firm’s financial data for period 2005-2011 obtained from Company Commission of Malaysia (CCM) was used for analysis. Results of the analysis could not prove any allegation of anticompetitive behavior and or exercise of market power by the integrators along the supply chain. However, the Farm level market is moderately concentrated over the study period indicated by the CR4 61.9% and HHI 2179. The overall performance of the industry based on results of the profitability ratio suggests the industry is doing quite well over the study period. The results of the 2SLS analysis show that concentration variable is significant and positively influences advertising. Furthermore concentration is positively related to profit and there is a two-way cause and effects existed between market concentration and industry behavior.